Toxicity of White Turi Stem Bark Extract on Mice: Toksisitas Ekstrak Kulit Batang Turi Putih pada Mencit - Anisatus Shalihah Amalia; Jamilatur Rohmah (Academia Open, 2023)
General background the use of traditional medicinal plants has gained attention due to their potential therapeutic benefits and safety. Specific background among these, Sesbania grandiflora (L.) Pers., commonly known as white turi, is recognized for its various bioactive compounds. However, there is a knowledge gap regarding the toxicity of its stem bark extract, particularly concerning its effects on vital organs such as the kidneys. Aims this study aims to evaluate the toxicity of white turi stem bark extract on mice by determining the LD50 and assessing kidney health through biochemical parameters such as Blood Urea Nitrogen (BUN) and creatinine levels.The results indicate no significant toxic symptoms or mortality in the treated mice, with macroscopic kidney observations showing reddish-brown coloration and a consistent texture resembling red kidney beans.Novelty this study provides novel insights into the safety profile of Sesbania grandiflora stem bark extract, suggesting that it does not pose significant renal toxicity. Implications these findings support its traditional use while encouraging further research into its pharmacological properties. Highlights: No significant toxic symptoms observed in treated mice. Macroscopic kidney analysis indicated no severe damage. Statistical results confirmed no renal toxicity at various extract doses. Keywords: Sesbania Grandiflora, Toxicity, LD50, Kidneys, Mice